ИНГЛИЗ ВА ҚОРАҚАЛПОҚ ТИЛЛАРИ КОМПАРАТИВ ФРАЗЕОЛОГИК БИРЛИКЛАРИ АНТОНИМИЯСИ - Сапаров, С.П. (SCIENCE and SOCIETY, 2023)
This article provides an analysis of the antonymy of comparative phraseological units of the English and Karakalpak languages. In this article, the problem of phraseological antonymy is singled out as a category opposite to phraseological synonymy and from a scientific point of view, is studied in close connection with it.